2018
DOI: 10.1103/physrevlett.120.253002
|View full text |Cite
|
Sign up to set email alerts
|

Suppressed Solitonic Cascade in Spin-Imbalanced Superfluid Fermi Gas

Abstract: Cold atoms experiments offer invaluable information on superfluid dynamics, including decay cascades of topological defects. While the cascade properties are well established for Bose systems, our understanding of their behavior in Fermi counterparts is very limited, in particular in spin-imbalanced systems, where superfluid (paired) and normal (unpaired) particles naturally coexist giving rise to complex spatial structure of the atomic cloud. Here we show, based on a newly developed microscopic approach, that… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
33
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 37 publications
(35 citation statements)
references
References 42 publications
2
33
0
Order By: Relevance
“…Spin reversed components of quasiparticle wavefunctions can be obtained via symmetry relation u n,↑ → v * n,↑ , v n,↓ → u * n,↓ and E n → −E n . The framework has been extensively tested over last years, and it proved to provide an accurate description of various dynamical properties of the strongly interacting Fermi gas, including generation and proliferation of quantum vortices [23] or dynamics of solitonic cascades [15,24]. More details related to technical aspects of solving TDASLDA equations we provide in the Appendix A.…”
Section: A Frameworkmentioning
confidence: 99%
“…Spin reversed components of quasiparticle wavefunctions can be obtained via symmetry relation u n,↑ → v * n,↑ , v n,↓ → u * n,↓ and E n → −E n . The framework has been extensively tested over last years, and it proved to provide an accurate description of various dynamical properties of the strongly interacting Fermi gas, including generation and proliferation of quantum vortices [23] or dynamics of solitonic cascades [15,24]. More details related to technical aspects of solving TDASLDA equations we provide in the Appendix A.…”
Section: A Frameworkmentioning
confidence: 99%
“…Recently, Magierski et al reported on a somewhat related physical system. In polarized systems, one can create unexpectedly stable spatially localized spin polarized droplets, with a similar change in the phase of the pairing gap across the boundary of these droplets …”
Section: Slda For Cold Atomic Gases Nuclei and Neutron Star Crustmentioning
confidence: 99%
“…Equation ( 7) was solved self-consistently, and the Broyden algorithm was applied to improve the convergence rate [55,56]. The calculations were executed with the use of W-SLDA Toolkit [36,38,57].…”
Section: Frameworkmentioning
confidence: 99%
“…This property significantly limits the possible forms of an energy density functional (EDF), and it allows for the successful formulation of the DFT framework for the UFG-the approach being in principle exact; see for a review [33]. The framework has been already applied for studies of quantum vortices [34][35][36][37], revealing a remarkable agreement with experiment [38]. Also, it admits the development of the FFLO state at unitarity [39].…”
Section: Introductionmentioning
confidence: 99%